Ecofeminism and an ethic of care: Developing an eco-jurisprudence - Cross, Carin Lesley (Acta Academica: Critical views on society, culture and politics, 2018)
This article looks into the damaging effect of the disintegrated relationship between humanity and nature. The current relationship we have with nature is hierarchal and fragmented because it is rooted in a culture of separation created by a ‘masculine’ modernity. The patriarchal values of rationality and power have othered the natural environment and women. In order to prevent irreparable ecological destruction, we need to change the relationship between humanity and nature to one that is ecologically responsive. I examine how ecofeminist literature enables us to challenge the hierarchical structure created by dualisms thereby uprooting the current patriarchal oppressive system. It reveals how an ethic of care approach can transcend the modern patriarchal structures that have promoted dominion over nature and contextually and narratively recreate the human and nature relationship. The value of this research lies in the fact that central to an ethic of care is the respect and care for all earthly beings, an ethic which listens to, and is responsive to the diversity of all ‘environmental voices’.